2021
DOI: 10.1101/2021.07.12.452030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human engineered skeletal muscle of hypaxial origin from pluripotent stem cells with advanced function and regenerative capacity

Abstract: SummaryHuman pluripotent stem cell derived muscle models show great potential for translational research. Here, we describe developmentally inspired methods for derivation of skeletal muscle cells and their utility in three-dimensional skeletal muscle organoid formation as well as skeletal muscle tissue engineering. Key steps include the directed differentiation of human pluripotent stem cells to embryonic muscle progenitors of hypaxial origin followed by primary and secondary fetal myogenesis into hypaxial mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Regeneration: Several rodents and human models have demonstrated that functional regeneration of skeletal muscle by satellite cells is recapitulated in vitro [ 86 , 134 , 158 , 229 ]. It would be important to extend these findings to neuromuscular disease entities to dissect if particular mutations or disease states affect muscle stem cell function in an experimental setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regeneration: Several rodents and human models have demonstrated that functional regeneration of skeletal muscle by satellite cells is recapitulated in vitro [ 86 , 134 , 158 , 229 ]. It would be important to extend these findings to neuromuscular disease entities to dissect if particular mutations or disease states affect muscle stem cell function in an experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…Human induced pluripotent stem cells (iPSC) are another valuable source of skeletal myocytes. A number of efficient directed differentiation protocols have been introduced to derive skeletal myocyte from iPSC [ 82 , 83 , 84 , 85 , 86 , 87 ]. All of them aim to recapitulate the embryonic development of skeletal muscle in cell culture by temporal modification and simulation of developmental cues.…”
Section: From 2d Cell Culture To Human Organs-on-a-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the immature state of the cells and the small X-ray spot size, the diffraction signal of the actomyosin lattice was quite low [226]. Nonetheless, progress in development of EHM patches of more mature cells gives hope for a detailed structural analysis [337,338]. Furthermore, the structural changes of the sarcomeric structure caused by genetic diseases such as Duchenne Muscle dystrophy could be investigated in a follow up experiment.…”
Section: Structural Analysis Of Cardiac Cells and Tissue On The Nanos...mentioning
confidence: 99%